Pierre Bec et sa contribution à une typologie des genres lyriques médiévaux, questions d’histoire des sciences et d’épistémologie, entre structuralisme et pratique occitaniste - Marjolaine Raguin-Barthelmebs (Lengas)
This paper proposes a study of the contribution of Pierre Bec to create a typology of the French medieval lyric poetry. Considering its thought and practice it can be considered that he was very influenced in his work by the development of structuralist theories and his self-engagement to serve the Occitan cultural revival between 1960 and 1980. Great philologist, Pierre Bec had the intelligence to embrace in a single glance the whole romance tradition, and particularly the French and Occitan medieval literatures.